1998
DOI: 10.1097/00000372-199806000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the Pathogenesis of Cutaneous Lupus Erythematosus

Abstract: Defective regulation of apoptosis may play a role in the development of autoimmune diseases such as systemic lupus erythematosus, in which the skin is a prominent target. To our knowledge, however, the nature of epidermal changes in cutaneous lupus erythematosus (LE) has not previously been investigated. We investigated the involvement of apoptosis in cutaneous LE. A total of 44 lesional skin samples from patients with cutaneous LE, 44 skin samples from patients with scleroderma, five skin specimens from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 38 publications
7
36
0
2
Order By: Relevance
“…Interestingly, nonlesional skin from patients with CLE also revealed a significantly higher count of epidermal apoptotic nuclei compared with normal skin. This finding of increased apoptosis in skin biopsy specimens from primary lesions of patients with CLE is in accordance with the findings in several published reports (45)(46)(47). In contrast to our study, in some of these studies apoptotic keratinocytes were observed in the entire epidermis, which might be explained by background labeling when performing the TUNEL technique under more relaxed conditions (48,49).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, nonlesional skin from patients with CLE also revealed a significantly higher count of epidermal apoptotic nuclei compared with normal skin. This finding of increased apoptosis in skin biopsy specimens from primary lesions of patients with CLE is in accordance with the findings in several published reports (45)(46)(47). In contrast to our study, in some of these studies apoptotic keratinocytes were observed in the entire epidermis, which might be explained by background labeling when performing the TUNEL technique under more relaxed conditions (48,49).…”
Section: Discussionsupporting
confidence: 93%
“…9 An important morphologic distinction from necrosis lies in the fact that apoptotic cell death lacks inflammation. 12 There are strong indications that apoptosis plays an important regulatory role in various disease processes such as cancer, 13,14 autoimmune diseases, 15,16 and others. [17][18][19][20][21] Increasing evidence suggests that alterations in the genetic control of cell survival and elimination seem to be important regulators in these disease states.…”
Section: Discussionmentioning
confidence: 99%
“…3B). CD8 cytotoxic T cells recruited to lesional skin by IFN-inducible chemokines (Blomberg et al 2001;Farkas et al 2001;Wenzel et al 2005), are retained the major responsible for this damage via the perforin and granzyme pathway (Blanco et al 2005), resulting in necrosis in basal and spinous epidermal layers (Chung et al 1998). It has been found that PDC strongly express granzyme B (GrB) either in lymphoid organs and inflamed skin (Rissoan et al 2002;Santoro et al 2005).…”
Section: J-pdc Co-localize With Cytotoxic T-cells In Areas Of Epithelmentioning
confidence: 99%